SARC‐F questionnaire identifies physical limitations and predicts post discharge outcomes in elderly patients with cardiovascular disease. Issue 1 (1st January 2018) - Tanaka, Shinya; Kamiya, Kentaro; Hamazaki, Nobuaki; Matsuzawa, Ryota; Nozaki, Kohei; Ichinosawa, Yuta; Harada, Manae; Nakamura, Takeshi; Maekawa, Emi; Noda, Chiharu; Yamaoka‐Tojo, Minako; Matsunaga, Atsuhiko; et al.
Abstract: Background: A simple and inexpensive sarcopenia screening tool would be beneficial in clinical practice. This study was performed to determine whether SARC‐F questionnaire can be used to identify physical limitations and poor prognosis in elderly cardiovascular disease (CVD) patients. Methods and results: The study population consisted of 257 Japanese patients ≥65 years old admitted to our hospital for CVD. Prior to discharge from hospital, SARC‐F, handgrip strength, usual gait speed, short physical performance battery score, and 6‐minute walking distance were measured in all patients. The patients were divided into two groups according to SARC‐F score: SARC‐F <4 and SARC‐F ≥4. The study endpoint was the first occurrence of all‐cause emergency readmission or all‐cause mortality. The prevalence rate of SARC‐F ≥4 was 26.8%, and increased with age and number of comorbidities. Even after adjusting for covariates, physical function was significantly poorer and the risks of physical function measurements below the critical cut‐off values were higher in the SARC‐F ≥4 group compared to the SARC‐F <4 group. Sixty (23.3%) patients were readmitted and 17 (6.6%) died over a median follow‐up period of 11 months (interquartile range: 6–13 months). SARC‐F score was a significant predictor of adverse events after discharge. Patients with SARC‐F ≥4 showed higher event risk than those with SARC‐F <4 (adjusted hazard ratio: 1.78; 95% confidence interval: 1.03–3.07; P = 0.040). Conclusions: SARC‐F questionnaire is useful to identify patients at high risk of physical limitations and to predict post‐discharge outcomes in elderly CVD patients.